2023
DOI: 10.3390/ijms24044004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis: Types, Effects, Markers, Mechanisms for Disease Progression, and Its Relation with Oxidative Stress, Immunity, and Inflammation

Abstract: Most chronic inflammatory illnesses include fibrosis as a pathogenic characteristic. Extracellular matrix (ECM) components build up in excess to cause fibrosis or scarring. The fibrotic process finally results in organ malfunction and death if it is severely progressive. Fibrosis affects nearly all tissues of the body. The fibrosis process is associated with chronic inflammation, metabolic homeostasis, and transforming growth factor-β1 (TGF-β1) signaling, where the balance between the oxidant and antioxidant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 147 publications
0
22
0
Order By: Relevance
“…In many tissues affected by fibrotic diseases, αSMA expression levels were used to identify myofibroblasts, the major collagen-producing cell type in fibrotic tissues [ 22 , 23 ]. Immunofluorescence analysis revealed that αSMA-positive cells were increased 3 to 4-fold after IL-13 or IL-4 stimulation in C3H mice ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…In many tissues affected by fibrotic diseases, αSMA expression levels were used to identify myofibroblasts, the major collagen-producing cell type in fibrotic tissues [ 22 , 23 ]. Immunofluorescence analysis revealed that αSMA-positive cells were increased 3 to 4-fold after IL-13 or IL-4 stimulation in C3H mice ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…[3,4] Notably, sustained stress sheltering by sutures at the mid-to-late healing stage might substantially hinder the positive mechanical effects on RC regeneration since the superior tissue healing and ECM remodeling processes are highly sensitive to mechanical stimulus. [25,35,60,61] Therefore, the incremental mechanobiological response of the healing tissue induced by progressive suture degradation may facilitate tissue healing and ECM remodeling for improving RC regeneration (Figure 3a).…”
Section: Hierarchical Micro-nano Tc-nyss-induced Incremental Mechanob...mentioning
confidence: 99%
“…Instead, persistent chronic inflammation and continuous vascularization would result in pathological fibrosis and tendon scarring, both harmful to RC regeneration. [35,36] A favorable environment for RC regeneration will be created by designing functional sutures specifically suited to the phased-matching biological healing requirements in this situation. [37] Therefore, in this study, we first used Poly(DL-lactide-coglycolide) (PLGA) to synthesize nanoyarns (nys), which were further braided into surgical sutures (nySS) with a triple helical and hierarchical micro-nano structure, mimicking the histological morphologies and micro-nano sizes of the RC tendon and interfascicular matrix (IFM) collagens.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of organ fibrosis, oxidative stress plays a critical role in the initiation and progression of the fibrotic process, 29 which is characterized by the excessive deposition of ECM proteins, and leads to the progressive loss of organ function 30 . Several studies have shown that oxidative stress can promote fibrosis by inducing the activation of fibro‐genic cells such as fibroblasts and myofibroblasts 31 …”
Section: Oxidative Stress and Its Role In Organ Fibrosismentioning
confidence: 99%
“…26 Moreover, ROS can inhibit the activity of matrix metalloproteinases (MMPs), which are enzymes that degrade ECM proteins, thereby impairing the process of ECM turnover and promoting fibrosis. 27,28 In the context of organ fibrosis, oxidative stress plays a critical role in the initiation and progression of the fibrotic process, 29 which is characterized by the excessive deposition of ECM proteins, and leads to the progressive loss of organ function. 30 Several studies have shown that oxidative stress can promote fibrosis by inducing the activation of fibro-genic cells such as fibroblasts and myofibroblasts.…”
Section: Oxidative S Tre Ss and Its Role In Org An Fib Ros Ismentioning
confidence: 99%